How Audience Diversity Affects Consumers' Creation of Brand Posts on Facebook: A Cross Cultural Examination. Issue 3 (4th May 2022) - Kitirattarkarn, Gauze Pitipon; Araujo, Theo; Neijens, Peter
ABSTRACT: The purpose of this study is to investigate cultural influence on the creation of brand-related posts on Facebook, with a particular focus on the mediating roles of the diversity of user audiences, as well as the intensity of Facebook use. The online survey was conducted with a representative sample of respondents from South Korea, Thailand, the Netherlands, and the United States (N = 802). The findings show that cultural differences at both personal and national levels play a role for social relationships between users and their audiences with consequences for the creation of brand posts. Specifically, as a result of audience diversity, users in individualistic cultures create brand-related content more frequently than users in collectivistic cultures, partly as a consequence of their higher Facebook use.